2019
DOI: 10.3126/jnphyssoc.v5i1.26876
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Orientation of Galaxies in Supercluster S[195+027+0022]

Abstract: We present a study of spin vector orientation of 1198 SDSS (Sloan Digital Sky Survey) galaxies in Super cluster S[195+027+0022] having red shift 0.07 to 0.09. The databases of these galaxies are taken from SDSS (Sloan Digital Sky Survey) 7th and 9th data release. We have converted two dimensional data to three-dimensional by Godlowskian Transformation using position angle-inclination angle method. We intend to find non-random effects in the spatial orientation of galaxies in Super cluster. No preferred alignme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Malla et al, [15][16][17][18] studied the non-random orientation of spin vector of supercluster S[202-002+0084] in 2019 having to mean redshift 0.084, supercluster S[195+027+0022] in 2019 that had redshift in the range 0.07 to 0.09, supercluster S[227+006+0078] in 2020 that had redshift in the range 0.07to 0.09 and supercluster S[231+030+0117] in 2020 that had redshift in the range 0.107 to 0.123. In all these three studies, they found that spatial orientation and projection of spin vector in all samples had not preferred alignments and which implies that random orientation and projection of spin vector with respect to the equilateral coordinate system.…”
Section: Comparison With Previous Workmentioning
confidence: 98%
“…Malla et al, [15][16][17][18] studied the non-random orientation of spin vector of supercluster S[202-002+0084] in 2019 having to mean redshift 0.084, supercluster S[195+027+0022] in 2019 that had redshift in the range 0.07 to 0.09, supercluster S[227+006+0078] in 2020 that had redshift in the range 0.07to 0.09 and supercluster S[231+030+0117] in 2020 that had redshift in the range 0.107 to 0.123. In all these three studies, they found that spatial orientation and projection of spin vector in all samples had not preferred alignments and which implies that random orientation and projection of spin vector with respect to the equilateral coordinate system.…”
Section: Comparison With Previous Workmentioning
confidence: 98%